PERANCANGAN BUKU RESEP MEMASAK KUE TRADISIONAL SUMATERA BARAT BERBAHAN DASAR KETAN - TISZA FERAHMA, Hendra Afriwan, S.Sn., M.Sn., Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Not everyone knows how to make traditional cakes, especially West Sumatra local cakes made from rice and glutinous rice flour which often appear in traditional events or family events. Meanwhile, a recipe book that specifically contains recipes from West Sumatra-based sticky rice cakes is still hard to find.The book